2017
DOI: 10.1111/dpr.12245
|View full text |Cite
|
Sign up to set email alerts
|

How new is the ‘new’ conditionality? Recipient perspectives on aid, country ownership and policy reform

Abstract: The concept of country ownership is central to international efforts to improve aid effectiveness. At the same time, policy reform in recipient countries continues to be a donor priority, given its potential to both reduce poverty and improve aid effectiveness. How effectively can donors promote reform while not undermining ownership?What role can be played by conditionality, discredited in recent decades but still widely used in altered form and linked to the provision of budget support? This article draws on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…He argues that budget support and related endeavours allow this type of close engagement, because they allow donors to become intimately involved in fiscal processes. In the Solomon Islands, Tonga and Tuvalu, Dornan (2017) argues that donors have used budget support to leverage specific policy reforms.…”
Section: The Rise and Fall Of Budget Support As Popular Aid Modalitymentioning
confidence: 99%
“…He argues that budget support and related endeavours allow this type of close engagement, because they allow donors to become intimately involved in fiscal processes. In the Solomon Islands, Tonga and Tuvalu, Dornan (2017) argues that donors have used budget support to leverage specific policy reforms.…”
Section: The Rise and Fall Of Budget Support As Popular Aid Modalitymentioning
confidence: 99%
“…Overton et al () highlight the agency exercised by Pacific Islanders in managing foreign aid flows. Dornan () examines conditionality and the limits to policy influence that donors exercise. There have also been studies of aid program changes on the donor side, the most relevant of which examine changes to Australia's and New Zealand's aid programs (see Banks et al () for a study of changes in New Zealand, and Corbett (), Corbett and Dinnen (), Day (), and Wood et al () for studies of changes to foreign aid in Australia).…”
Section: Literature On Aid In the Pacificmentioning
confidence: 99%
“…Murray and Overton () argue that such changes have reduced sovereignty of Pacific island countries. Dornan () is more optimistic and notes some improvements. Below, we use the quantitative data that are available to explore changes to foreign aid provided in the region over this period, focusing on variables that can be measured.…”
Section: Analysis Of Foreign Aid In the Pacificmentioning
confidence: 99%
“…Whitfield (2009a, p. 4) observed that the popularity of ownership in development diplomacy may be precisely because it is challenging to define, thereby obfuscating debates around decision‐making processes in development policy. The same may be observed in the academic realm, with contributions variously emphasizing ownership as developing country leadership (Graham, 2017; Booth, 2012), broad‐based consensus (Faust, 2010) or participation (Dornan, 2017). Building on Whitfield and Fraser’s (2010) observation that ownership may be expressed and pursued as commitment and control, a recent study suggested that ownership should be viewed as encompassing both the substance and process of co‐operation.…”
Section: Defining and Researching Ownershipmentioning
confidence: 74%